New developments in theoretical and conceptual approaches to job stress - Perrewe, Pamela L.; Ganster, Daniel C. (Emerald, 2010)
The objective of this series is to promote theory and research in the increasingly growing area of occupational stress, health and well being, and in the process, to bring together and showcase the work of the best researchers and theorists who contribute to this area. Questions regarding work stress span many disciplines and many specialized journals. It is increasingly difficult to track, and even harder to integrate, the work from these diverse fields. Our plan is to provide a multidisciplinary and international collection that gives a thorough and critical assessment of knowledge, and major gaps in knowledge, on occupational stress and well being. Furthermore, because we will be publishing monograph-length conceptual papers, our interest is in promoting the careful development of truly path-breaking contributions that can significantly advance theory and provide specific directions for future work.
Keywords: Job stress.; Psychology, Industrial.; Work -- Psychological aspects.; elektronické knihy; electronic books